2011
DOI: 10.1074/jbc.m111.274456
|View full text |Cite
|
Sign up to set email alerts
|

The Highly Conserved Glycan at Asparagine 260 of HIV-1 gp120 Is Indispensable for Viral Entry

Abstract: Carbohydrate-binding agents bind to the N-glycans of HIV-1 envelope gp120 and prevent viral entry. Carbohydrate-binding agents can select for mutant viruses with deleted envelope glycans. Not all glycosylation motifs are mutated to the same extent. Site-directed mutagenesis revealed that deletions destroying the highly conserved 260 NGS 262 glycosylation motif resulted in non-infectious virus particles. We observed a significant lower CD4 binding in the case of the N260Q mutant gp120 virus strains, caused by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 46 publications
5
33
0
Order By: Relevance
“…Use of pharmacological inhibitors and lectins suggested that, as expected, glycosylation is involved in cell fusion, confirming and expanding previous reports (26,31,32) (Fig. 1).…”
Section: Discussionsupporting
confidence: 91%
“…Use of pharmacological inhibitors and lectins suggested that, as expected, glycosylation is involved in cell fusion, confirming and expanding previous reports (26,31,32) (Fig. 1).…”
Section: Discussionsupporting
confidence: 91%
“…N-Glycans include three basic structures, namely, high-mannose (i.e., oligomannose), hybrid, and complex glycans, all of which are present on HIV-1 Env (4-7). Importantly, N-glycans shield the Env backbone and have been shown to play key roles in determining the Env structure, epitope exposure, and, consequently, antigenicity, immunogenicity, antibody neutralization, infectivity, and carbohydrate and receptor binding (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…N-Glycans include three basic structures, namely, high-mannose (i.e., oligomannose), hybrid, and complex glycans, all of which are present on HIV-1 Env (4-7). Importantly, N-glycans shield the Env backbone and have been shown to play key roles in determining the Env structure, epitope exposure, and, consequently, antigenicity, immunogenicity, antibody neutralization, infectivity, and carbohydrate and receptor binding (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).The position of N-linked glycans on glycoproteins is genetically encoded, whereas the types of glycans at a given Asn in the consensus Asn-X-Ser/Thr-X sequence (where X is not Pro) are determined by the glycan branching processes in the cell endoplasmic reticulum and Golgi apparatus (21). However, some glycoproteins, including HIV-1 gp120, demonstrate protein-specific glycosylation (22)(23)(24)(25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported that glycan deletions in the HIV-1 gp120 V1/V2 domains severely compromise viral infectivity and sensitize the mutant virus strains to carbohydrate-binding agents [56]. Furthermore, some specific Nglycosylation sites are indispensable for efficient viral entry (such as Asn 260 ) [57]. Thus, a resistance pattern directed to the elimination of N-glycosylation sites of gp120 could be of interest in enhancing immunosuppression of the pathogen.…”
Section: Carbohydrate-binding Agents (Cbas): Glycans Of Hiv As Targetsmentioning
confidence: 99%